A study on appetite of overweight/obese patients with type 2 diabetes mellitus based on multimodal magnetic resonance imaging - Mingxuan Gao; Liya Gong; Yanmei Zeng; Dongling Li; Junyan Wen; Ying Guo; Zhujia Li; Jingwen Luo; Chunling Chen; Ge Wen (Frontiers in Neuroimaging)
PurposeTo investigate the alterations of brain structure and function in brain regions related to ingestive desire in overweight/obese T2DM patients, and the correlation with clinical data.Subjects52 patients with overweight/obese type 2 diabetes mellitus (T2DM group), 62 patients with simple obesity (OB group), and 40 healthy subjects (HC group).AssessmentBy means of gray matter morphometric indices (cortical thickness, surface area, etc.), resting-state functional magnetic resonance indices (ALFF, ReHo, FC) and DTI eigenvalues (AD, MD, etc.).Statistical testsComparisons among the three groups were made using one-way ANOVA, bonferroni post hoc test for two-way comparisons, and spearman for correlation analysis.ResultsCompared with the OB and HC groups, the T2DM group showed a significant reduction in cortical thickness in the bilateral superior frontal gyrus, inferior frontal gyrus orbital region, and the lower part of the right middle frontal gyrus, and the functional connectivity of the prefrontal cortex showed a significant trend of enhancement. Meanwhile, compared with the HC group, the T2DM group showed a significant decrease in FA (fractional anisotropy) values in the midline region of the orbitofrontal cortex bilaterally, and the left inferior frontal gyrus orbital region also showed a significant decrease in FA values, whereas AD (axial diffusivity), MD (mean diffusivity), and RD (radial diffusivity) increased significantly.Data conclusionT2DM patients have significant alterations in gray matter structure, brain white matter integrity and brain function, and most of the brain regions with significant differences are in the prefrontal cortex, which confirms that the abnormal desire to ingest in T2DM patients is closely related to the functional alterations of the reward system, and that observing the brain function and structural changes of the reward loop through imaging may help in the early diagnosis and treatment of overweight/obese T2DM patients.